Quick setting composition based on steelmaking metallurgical slag - Khamatova, Alsu; Khozin, Vadim; Khohryakov, Oleg; Yakovlev, Grigory (International Conference “Environmental Engineering”, 2017)
The article deals with the problem of utilizing steelmaking slag from the production of rapid hardening composition in Izhstal, CJSC (Izhevsk, Russia), determining its physical and mechanical characteristics, and applying its properties for renovation and reconstruction. The physical and mechanical characteristics of the developed mortar exceed the existing analogues in many parameters (setting speed, strength). Dry mortar has a short setting time (the end of setting occurs 3,5 minutes after mixing with water at W/S = 0,3), its strength being 66,8 MPa after 28 days of normal hardening. The results show this mortar can be used for emergency renovation work to stop leaks in concrete, stone and brick structures. The studies were conducted using the methods of physical and chemical study of the structure and properties of the produced composition. The developed composition helps reduce the environmental pressure in places of electric steelmaking slag dump.